(untitled) (Journal of Economic Additions, 2019)
This paper aims to discuss the inability of traditional cost methods to provide appropriate information about production environment in Sudan. One of the paper goals is to show the limitation of traditional cost accounting system in meeting the production needs in such environment. The most important findings are: 1. The success of activity based costing (ABC) in measuring production costs accurately, depends on cost caused activities 2. Using descriptive methods may not measure accurately the production costs. 3. There is statistical relationship between ABC system, and accurate production costs measurement. Recommendations: 1. Statistical, arithmetical and descriptive methods are needed to measure production cost activities accurately. 2. Close follow up to cost cussed activities is also needed. 3. Cost and management accounting methods are to be developed for more investigation and research about how to measure production costs. Key words: modern techniques, cost accounting, measurement and analysis, Internal industrial cost